Research Trends in Cyber-Physical Systems within Information Systems: A Bibliometric Approach - Judijanto, Loso; Baharuddin, Baharuddin (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric analysis of research trends in Cyber-Physical Systems (CPS) within the Information Systems (IS) domain, utilizing data from the Scopus database (2010–2025) and analyzed using VOSviewer. By examining keyword co-occurrence, overlay mapping, density visualization, and collaboration networks, the study identifies the thematic structure, intellectual linkages, and global research collaborations shaping the CPS–IS landscape. Results reveal that CPS research is highly interdisciplinary, with central themes including internet of things, network security, machine learning, and information management, while emerging areas such as digital twin, intrusion detection, and false data injection attacks are gaining momentum. The overlay visualization indicates a recent shift toward AI-driven security and optimization in CPS applications. Authorship and country collaboration analyses highlight China, the United States, Germany, and India as leading contributors with extensive international linkages. This study contributes to the theoretical understanding of CPS as an integrated socio-technical construct in IS and provides practical insights for aligning research, policy, and industrial strategies with evolving technological priorities in the era of Industry 4.0.